Estudo epidemiológico do primeiro surto de melioidose no Brasil - Rolim, Dionne Bezerra (2004)
The first melioidosis outbreak in Brazil happened when four adolescents presented a severe case of the disease, with pneumonia and sepsis, in a small rural community in the Northeast of Brazil, in February 2003. Burkolderia pseudomallei were identified through blood culture in one case, firstly using conventional methods and then confirmed by PCR. The diagnosis was presumptive in the other three cases. The preliminary epidemiological investigation identified the possible contributing factors: onset of the symptoms during the rainy season, exposure of the cases to the soil and water in leisure activities, presence of a river dam close to the residence, the area around the house had been exposed to heavy rain two days before the symptoms, and the house had dirt floor. The fact that the children got sick on the same day, points to a possible common and simultaneous exposure. The dam was identified as the most probable place of contamination, and the transmission mechanism might have happened through aspiration, inhalation or ingestion of water from the dam. The recent outbreak rises the important questioning about the existence of the disease in Brazil, and shows the need of a detailed environmental study to understand its occurrence.